2017
DOI: 10.1063/1.4996409
|View full text |Cite
|
Sign up to set email alerts
|

Charge separation and carrier dynamics in donor-acceptor heterojunction photovoltaic systems

Abstract: Electron transfer and subsequent charge separation across donor-acceptor heterojunctions remain the most important areas of study in the field of third-generation photovoltaics. In this context, it is particularly important to unravel the dynamics of individual ultrafast processes (such as photoinduced electron transfer, carrier trapping and association, and energy transfer and relaxation), which prevail in materials and at their interfaces. In the frame of the National Center of Competence in Research “Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…A subband positive absorption feature was also observed in the low photon energy region of 760 to 830 nm (Figure b), which can be attributed to the phenomena of electroabsorption (EA). EA is a Stark effect due to the local electric field induced by the correlated charge pair dipoles in the heterostructures. , The time-resolved TAS revealed that the lifetime of this short-lived EA signal at 810 nm is only 440 fs (Figure c); only this signal is short-lived compared to other features that persist on longer time scales. These charge pair dipoles are direct evidence of the enhancement of the built-in voltage due to the localized electric field inside the 2D/3D bilayer perovskite heterostructures. , A redshift is also noted in the PB peak due to the renormalization occurring due to EA phenomena following excitation of the 2D perovskite above its bandgap (Figure S5).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A subband positive absorption feature was also observed in the low photon energy region of 760 to 830 nm (Figure b), which can be attributed to the phenomena of electroabsorption (EA). EA is a Stark effect due to the local electric field induced by the correlated charge pair dipoles in the heterostructures. , The time-resolved TAS revealed that the lifetime of this short-lived EA signal at 810 nm is only 440 fs (Figure c); only this signal is short-lived compared to other features that persist on longer time scales. These charge pair dipoles are direct evidence of the enhancement of the built-in voltage due to the localized electric field inside the 2D/3D bilayer perovskite heterostructures. , A redshift is also noted in the PB peak due to the renormalization occurring due to EA phenomena following excitation of the 2D perovskite above its bandgap (Figure S5).…”
Section: Resultsmentioning
confidence: 95%
“…EA is a Stark effect due to the local electric field induced by the correlated charge pair dipoles in the heterostructures. , The time-resolved TAS revealed that the lifetime of this short-lived EA signal at 810 nm is only 440 fs (Figure c); only this signal is short-lived compared to other features that persist on longer time scales. These charge pair dipoles are direct evidence of the enhancement of the built-in voltage due to the localized electric field inside the 2D/3D bilayer perovskite heterostructures. , A redshift is also noted in the PB peak due to the renormalization occurring due to EA phenomena following excitation of the 2D perovskite above its bandgap (Figure S5). The PB feature displayed an enhancement, whereas the broad absorption below 650 nm and the EA above 750 indicated decay in the early time spectrum (Figure b).…”
Section: Resultsmentioning
confidence: 95%
“…61,62 It also plays a crucial role in charge separation in organic photovoltaics (Voss et al, DOI: 10.1039/ c8fd00210j). 63 ET at the molecular/solid interface is also crucial in the function of photocatalytic reactions, 12,64,65 molecular electronics, 66 photo-electrolysis, 67 and photography. 68,69 In many of these systems, the ET is extremely fast (few femtoseconds) [70][71][72][73] such that it cannot be described by a simple rate description, and quantum-chemical methods are needed, oen with time-domain modelling.…”
Section: Modelling Electron Transfermentioning
confidence: 99%
“…But with the advent of attosecond science [4] the question "Does tunnelling take time, and if yes, how much?" has gained a lot of new interest, since electron dynamics often include quantum tunnelling portions, be that in biological processes such as photosynthesis [5] or charge transport in semiconductors [6], tunnelling ionisation as the first step for high-order harmonic generation (HHG) spectroscopy [7], photoelectron holography [8], laser induced electron diffraction (LIED) [9] or many more.…”
Section: Introductionmentioning
confidence: 99%